Inverted formin 2‐related Charcot‐Marie‐Tooth disease: extension of the mutational spectrum and pathological findings in Schwann cells and axons. Issue 1 (March 2015) - Roos, Andreas; Weis, Joachim; Korinthenberg, Rudolf; Fehrenbach, Henry; Häusler, Martin; Züchner, Stephan; Mache, Christoph; Hubmann, Holger; Auer‐Grumbach, Michaela; Senderek, Jan
Abstract Mutations in the gene encoding inverted formin FH2 and WH2 domain‐containing protein (INF2), a Cdc42 effector involved in the regulation of actin dynamics, cause focal segmental glomerulosclerosis (FSGS) and intermediate Charcot‐Marie‐Tooth neuropathy combined with FSGS (FSGS–CMT). Here, we report on six patients from four families with sensorimotor polyneuropathy and FSGS. Nerve conduction velocities were moderately slowed, and amplitudes of sensory and motor potentials were decreased. One patient had internal hydrocephalus and was intellectually disabled. Molecular genetic testing revealed two known and two novel missense mutations in the second and fourth exons of the INF2 gene. Investigations of one nerve biopsy confirmed the diagnosis of intermediate‐type CMT and revealed occasional abnormal in‐ and outfoldings of myelin sheaths and expansions of the endoplasmic reticulum in axons and Schwann cells. While earlier reports suggested that mutations causing FSGS‐CMT are restricted to exons 2 and 3 of the INF2 gene, we found one CMT‐FSGS causing mutation (p.Glu184Lys) in exon 4 extending the critical region of INF2 for rapid CMT‐FSGS molecular genetic diagnosis. Study of a nerve biopsy showed abnormalities that might be related to the known role of the INF2‐binding partner CDC42 in myelination.